In Operando Closed-cell Transmission Electron Microscopy for Rechargeable Battery Characterization: Scientific Breakthroughs and Practical Limitations. (1st June 2022) - Tao, Shiwei; Li, Ming; Lyu, Miaoqiang; Ran, Lingbing; Wepf, Roger; Gentle, Ian; Knibbe, Ruth
Abstract: Development of high-performance rechargeable batteries is hinged on a clear mechanistic understanding of the fundamental electrochemical processes. In operando transmission electron microscopy (TEM) provides a nanoscale insight into the dynamic microstructural evolution of battery components. The open-cell and closed-cell are the main configurations for in situ/operando TEM battery studies. While the open-cell configuration uses an ionic liquid or a solid electrolyte, the closed-cell configuration adopts a dynamic flow of a liquid electrolyte. As such, the processes observed in the closed-cell configuration more reliably reflect the electrochemical setup in most ion batteries under development. This also permits the observation of processes such as dendritic growth and solid electrolyte interphase formation, which cannot be observed in the open-cell configuration. However, the benefits of the closed-cell configuration come at the cost of imaging resolution. In this review, the opportunities and obstacles for current closed-cell in operando TEM systems is explored. This is done by highlighting and comparing the key findings between closed-cell and open-cell configurations where possible. These include Li-ion (LIBs) and the state-of-the-art Li-O2, Na-ion (NIBs), Na-O2 and Ca-ion batteries. Furthermore, the closed-cell in operando testing conditions are systematically consolidated including information on electrodes, electrolyte and flow parameters, TEM beam conditions and cell membrane thickness. This information is critical in ensuring the reliability and reproducibility of the experimental work. Finally, we address the challenges still faced with closed-cells and deliver future perspectives of in situ/operando TEM in rechargeable battery characterization. Graphical Abstract: ga1